Holistic Arabic Teaching Materials for Kurikulum Merdeka at State Islamic Higher Education Institutions (PTKIN): A Multisite Study - Nasir, Amin; Falah, Ahmad; Ali, Muhammad Adam Muhammad Abdel (Universitas Islam Negeri Raden Intan Lampung, 2026)
The increasing demand for effective Arabic language instruction in higher education has highlighted the need for more integrated and contextually meaningful teaching materials. In the context of Kurikulum Merdeka, this becomes particularly relevant as institutions are encouraged to develop flexible and competency-based learning designs. This article examines how holistic Arabic teaching materials are designed and enacted within Kurikulum Merdeka across State Islamic Higher Education Institutions (PTKIN) through a qualitative multisite case study. Data were generated from multiple sources, including: (1) curriculum and instructional documents (e.g., RPS, modules, and assessment artefacts), (2) non-participant classroom observations, and (3) semi-structured interviews and focus group discussions with programme leaders, lecturers, and students. The findings show that holism is operationalized as a curriculum bundle aligning outcomes, integrated-skill task pathways, media use, and assessment, rather than as a single textbook format. Islamic knowledge and socio-religious campus life function as authentic discourse domains that support input-interaction-output cycles, yet productive skills (speaking and writing) remain the main bottlenecks when formative feedback is weak. Transferability across PTKIN depends on alignment templates, shared rubrics, reusable task banks, and feasible feedback workflows. This study contributes to the literature on Arabic language pedagogy by conceptualizing holistic teaching materials as an integrated curriculum system and highlighting the critical role of assessment and feedback mechanisms in ensuring effective implementation across institutional contexts.